2022
DOI: 10.3389/fspas.2022.853676
|View full text |Cite
|
Sign up to set email alerts
|

External Forcing of the Solar Dynamo

Abstract: In this paper I examine whether external forcing of the solar dynamo on long timescales can produce detectable signal in the form of long term modulation of the magnetic cycle. This task is motivated in part by some recent proposals (Abreu et al., 2012; Astron. Ap., 548, A88; Stefani et al., 2021; Solar Phys., 296, 88), whereby modulation of the solar activity cycle on centennial and millennial timescales, as recovered from the cosmogenic radioisotope record, is attributed to perturbation of the tachocline dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
2
17
0
1
Order By: Relevance
“…This could be equivalent to having gravitational tidal amplitudes amplified from 1 mm to 1 km at the tachocline. This amplification could solve the problem of the "homeopathic" gravitational tidal energy contribution highlighted by Charbonneau (2022).…”
Section: A Possible Solar Amplification Of the Planetary Tidal Forcingmentioning
confidence: 96%
See 3 more Smart Citations
“…This could be equivalent to having gravitational tidal amplitudes amplified from 1 mm to 1 km at the tachocline. This amplification could solve the problem of the "homeopathic" gravitational tidal energy contribution highlighted by Charbonneau (2022).…”
Section: A Possible Solar Amplification Of the Planetary Tidal Forcingmentioning
confidence: 96%
“…Many authors suggest that solar cycles revealed in sunspot and cosmogenic records could derive from a deterministic non-linear chaotic dynamo (Weiss and Tobias, 2016;Charbonneau, 2020Charbonneau, , 2022. However, the assumption that solar activity is only regulated by dynamical and stochastic processes inside the Sun has never been validated mainly because these models have a poor hindcasting capability.…”
Section: Possible Physical Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…A related question that presents itself concerns the possible influence of tidal forces on convective motion 30 . While, due to the huge differences between the tidal and inertial forces in the solar convection zone 22,23 , any noticeable effect in this region seems extremely unlikely, convection is at least an attractive candidate for an experiment on helicity synchronization. In view of the significant challenges in carrying out liquid metal experiments on the very TI 21 , Rayleigh-Bénard(RB) convection may provide an interesting surrogate with nearly identical topological features.…”
Section: Introductionmentioning
confidence: 99%